The Existence of Fixed Points for a Different Type of Contractions on Partial b-Metric Spaces. (14th August 2021) - Nazam, Muhammad; Işik, Hüseyin; Javed, Khalil; Naeem, Muhammad; Arshad, Muhammad
Abstract : The aim of this study is to present fixed point results in the setting of partial b -metric spaces. A different type of contractions is used to prove fixed point results in the given space, which are real generalization of many well-known results. The readers are also provided with some very interesting examples to illustrate the feasibility of the proposed work.